2015
DOI: 10.1002/clc.22412
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of Positive Airway Pressure Therapy for Sleep‐Disordered Breathing in Heart Failure Patients With Preserved Left Ventricular Ejection Fraction

Abstract: Background: Right-heart dysfunction is associated with poor prognosis in heart failure with preserved left ventricular ejection fraction (HFpEF). It remains unclear whether sleep-disordered breathing (SDB) treatment using positive airway pressure (PAP) improves right-heart and pulmonary function and exercise capacity and reduces mortality rates of HFpEF patients. Hypothesis: PAP may improve right-heart and pulmonary function, exercise capacity and prognosis in HFpEF patients with SDB. Methods: One hundred nine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 42 publications
2
15
0
1
Order By: Relevance
“…Additionally, meta‐analysis has demonstrated that continuous positive airway pressure improves aortic stiffness in patients with OSA 40. We previously reported that the reduction of all‐cause mortality in HFpEF patients with SDB after positive airway pressure treatment might be partly due to improvement of aortic stiffness 41, 42. Thus, it is possible to speculate that SDB management using positive airway pressure improves the prognosis of HFpEF patients via a decrease in arterial stiffness, which is one of the important mechanisms underlying HFpEF, as we reported in our previous study.…”
Section: Discussionsupporting
confidence: 61%
“…Additionally, meta‐analysis has demonstrated that continuous positive airway pressure improves aortic stiffness in patients with OSA 40. We previously reported that the reduction of all‐cause mortality in HFpEF patients with SDB after positive airway pressure treatment might be partly due to improvement of aortic stiffness 41, 42. Thus, it is possible to speculate that SDB management using positive airway pressure improves the prognosis of HFpEF patients via a decrease in arterial stiffness, which is one of the important mechanisms underlying HFpEF, as we reported in our previous study.…”
Section: Discussionsupporting
confidence: 61%
“…In a study of 15 patients with HFpEF and severe OSA, diuretic use reduced systolic blood pressures and OSA severity and was associated with increased oropharyngeal junction area, suggesting contributions from resolving upper airway edema [111]. In 109 consecutive patients on HF medical therapy with moderate to severe sleep-disordered breathing, non-invasive positive pressure ventilation (NIPPV) has been shown to provide an improvement in right heart function and pulmonary function as well as a reduction in all-cause mortality [112]. However, in a study of 101 patients newly diagnosed with HFpEF on hospital admission, 58 patients underwent screening for sleep apnea which confirmed a diagnosis in 39 patients [113].…”
Section: Non-pharmacological Treatments For Htn In Hfpefmentioning
confidence: 99%
“…The six studies that examined the effect of treatment of sleep apnea in adults with HFpEF with positive airway pressure are described in Table 1. 3943 Four of these studies 39,40,42,43 had a prospective observational design 39,40,42 and two were randomized controlled trials with a control group that received usual care (i.e. cardiac medications).…”
Section: Resultsmentioning
confidence: 99%